2021
DOI: 10.3389/fimmu.2021.613438
|View full text |Cite
|
Sign up to set email alerts
|

Latent TGF-β Activation Is a Hallmark of the Tenascin Family

Abstract: Transforming growth factor-β (TGF-β) isoforms are secreted as inactive complexes formed through non-covalent interactions between bioactive TGF-β entities and their N-terminal pro-domains called latency-associated peptides (LAP). Extracellular activation of latent TGF-β within this complex is a crucial step in the regulation of TGF-β activity for tissue homeostasis and immune cell function. We previously showed that the matrix glycoprotein Tenascin-X (TN-X) interacted with the small latent TGF-β complex and tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 66 publications
1
17
0
2
Order By: Relevance
“…In the present study, we identified a 15-aa peptide (referred to as hTNX-FGFFFF with an aa sequence of GGLRIPFPRDCGEEM) located at the N-terminal part of the TNX-FG domain as the minimum region responsible for the induction of COL1A1 expression. Interestingly, this minimum region in the TNX-FG domain was not overlapped with some residues in loop 9 in the TNX-FG domain reported by Aubert et al (43), indicating that the 15-aa peptide would fail to interact directly with LAP and mature TGF-β1. However, the fact that SB525334 weakly suppresses the induction of COL1A1 expression with overexpression of hTNX-FGFFFF and integrin α11β1 as shown in Fig.…”
Section: Discussionmentioning
confidence: 65%
“…In the present study, we identified a 15-aa peptide (referred to as hTNX-FGFFFF with an aa sequence of GGLRIPFPRDCGEEM) located at the N-terminal part of the TNX-FG domain as the minimum region responsible for the induction of COL1A1 expression. Interestingly, this minimum region in the TNX-FG domain was not overlapped with some residues in loop 9 in the TNX-FG domain reported by Aubert et al (43), indicating that the 15-aa peptide would fail to interact directly with LAP and mature TGF-β1. However, the fact that SB525334 weakly suppresses the induction of COL1A1 expression with overexpression of hTNX-FGFFFF and integrin α11β1 as shown in Fig.…”
Section: Discussionmentioning
confidence: 65%
“…It is comprised of 200 kDa hexamers and possesses 511 isoforms, since it contains nine splice variable Fn III domains in addition to the eight constant ones, and a C-terminal FBG-like domain ( 96 ). The FBG domains, highly conserved among the Tenascin family members (TNC, tenascin R, tenascin W, and tenascin X), can dock with TGF-β small latent complex and activate latent TGF-β ( 97 ). In addition to sharing domains that can be unfolded by cell forces with Fn, TNC can bind Fn directly ( 98 ).…”
Section: Hemostasis and Ecmmentioning
confidence: 99%
“…As such, most of the TGF-β deposited in the extracellular space is inactive, although active TGF-β is observed in specific locations ( Barcellos-Hoff et al, 1994 ). Bioavailability of TGF-β is additionally regulated by TGF-β-binding proteins like fibromodulin and decorin which sequester TGF-β and prevent it from binding to specific TGF-β receptors ( Hinz, 2015 ; Khan and Marshall, 2016 ; Nastase et al, 2018 ; Aubert et al, 2021 ). Activation of latent TGF-β is a key step in the regulation of TGF-β-signaling activity.…”
Section: Transforming Growth Factor-β Signaling: Pathways and Mechanismsmentioning
confidence: 99%